Loss of RNA expression and allele-specific expression associated with congenital heart disease - David M. McKean (Nature Portfolio, 2016)
Congenital heart disease (CHD) is a disorder that occurs in ∼1% of live births. Here the authors describe a genome-wide allele-specific expression analyses in CHD patients, identifying five new genes involved in CHD and showing that paternally-expressed imprinted genes are monoallelic, while maternally-expressed imprinted genes are biallelic.